Congenital malformations and maternal risk factors in Campina Grande — Paraíba - Virgínia Rossana de Sousa Brito; Francisco Stélio de Sousa; Francisco Henrique Gadelha; Rafaella Queiroga Souto; Ana Raquel de Figueiredo Rego; Inacia Sátiro Xavier de França (Rev Rene)
This study aimed to determine the prevalence of children born with congenital malformations in maternities of Campina Grande — PB and the associated risk factors. Data were collected in three maternities through the certificates of live birth (CLB) issued during the period of 2003 and 2005. The association between the types of malformations and the variables was tested by Chi-square and Odds Ratio, by using the program SPSS 15.0. It was used significance p<0,05. 190 malformations were detected which were distributed in the following categories: morphological dysplasia with 90 cases (47.4%), histological dysplasia 49(25.8%), chemical dysplasia 1(0.5%), multiple malformations 34(17.9%) and not specified malformations 16(8.4%) cases. Other cases were also identified: hydrocephaly, anencephaly, Down syndrome, polydactyly, cleft lip and crooked feet. The conclusion was that there was no statistically significant association between social variables related to the mothers and congenital malformation. The significant number of illegible BC, or without specification of malformation, shows the need for more accuracy in form filling.